Spiders from Molise (Italy): state of knowledge, new faunistic data and taxonomic notes (Arachnida: Araneae) - Alessio Trotta (Fragmenta entomologica, 2020)
The spiderfauna of Molise includes 98 species belonging to 64 genera and 21 families; 48 species are firstly reported for this region, 19 are earlier record confirmed and 31 are earlier record to be confirmed. The following new combination and new synonymies are proposed: Zelotes caprearum (Pavesi, 1875) = Zelotes caporiaccoi Denis, 1953 (not Zelotes caporiaccoi Roewer, 1951) syn. n. = Zelotes denapes Platnick, 1993 syn. n.; Cozyptila nigristernum (Dalmas, 1922) comb. n. = Cozyptila thaleri Marusik and Kovblyuk, 2005 syn. n.